(untitled) (Communications in Mathematical Research, 2021)
In this paper, we obtain some sharp inequalities between the Ricci curvature and the squared mean curvature for bi-slant and semi-slant submanifolds in Kenmotsu space forms. Estimates of the scalar curvature and the k-Ricci curvature, in terms of the squared mean curvature, are also proved respectively.